NUMERICAL STUDY OF A COLLISION AVOIDANCE METHOD FOR MOBILE COLLABORATIVE ROBOTS IN A MULTI-USER ENVIRONMENT (Multidisciplinary Journal of Science and Technology, 2025)
The article presents a numerical study of the collision avoidance method for mobilecollaborative robots in a multi-user environment, which is a relevant task of modern robotics in theconditions of Industry 5.0. The proposed approach combines the principles of the mutual velocityobstacle model and the dynamic window method, which allows forming adaptive trajectories takinginto account moving agents and static obstacles. The numerical simulation demonstrates theeffectiveness of the algorithm in complex scenarios, where robots start from different positions andhead towards separate targets, maintaining safe distances during interaction. The results obtainedshow that even in cases of critical convergence, the system is able to correct trajectories and preventcollisions. Analysis of trajectories and minimum inter-agent distances confirms the logicalconsistency of the algorithm and its ability to dynamically adjust. Qualitative assessment indicatesthat the system achieves stability at the later stages of modeling, which is confirmed by the increasein distances between agents after resolving conflict situations. Thus, the developed method can beused as a basis for building intelligent traffic control systems in a multi-user environment.